In vivo electroporation of a codon-optimized BERopt DNA vaccine protects mice from pathogenic Mycobacterium tuberculosis aerosol challenge. (December 2018) - Tang, Jiansong; Cai, Yi; Liang, Jianguo; Tan, Zhiwu; Tang, Xian; Zhang, Chi; Cheng, Lin; Zhou, Jingying; Wang, Haibo; Yam, Wing-Cheong; Chen, Xinchun; Wang, Hui; et al.
Abstract: DNA vaccines have been extensively studied as preventative and therapeutic interventions for various infectious diseases such as tuberculosis, HIV/AIDS and influenza. Despite promising progresses made, improving the immunogenicity of DNA vaccine remains a technical challenge for clinical development. In this study, we investigated a tuberculosis DNA vaccine BER opt, which contained a codon-optimized fusion immunogen Ag85B-ESAT-6-Rv2660c for enhanced mammalian cell expression and immunogenicity. BER opt immunization through in vivo electroporation in BALB/c mice induced surprisingly high frequencies of Ag85B tetramer + CD8 + T cells in peripheral blood and IFN-γ-secreting CD8 + T cells in splenocytes. Meanwhile, the BER opt vaccine-induced long-lasting T cell immunity protected BALB/c mice from high dose viral challenge using a modified vaccinia virus Tiantan strain expressing mature Ag85B protein (MVTT-m85B) and the virulent M. tb H37Rv aerosol challenge. Since the BER opt DNA vaccine does not induce anti-vector immunity, the strong immunogenicity and protective efficacy of this novel DNA vaccine warrant its future development for M. tb prevention and immunotherapy to alleviate the global TB burden.